Actitud materna hacia la inmunización y calendario de vacunación del niño menor de 18 meses C.S. Victor Larco 2011 - Paredes Sánchez, Jackelin Joa (2011)
Job type research Quantitative Descriptive Correlation performed on children up to 18 months old Health Center Victor Larco - Trujillo, in order to determine the relationship between maternal attitude toward immunizations and compliance with the child's vaccination schedule up to 18 months. The universe consisted of 108 mothers of children up to age 18 months and the sample was 61 mothers who met the inclusion criteria. For data collection test was applied to mothers' attitudes toward immunizations and a Registration Form Schedule of Vaccination. The results are reported in tables and graphs. To determine the relationship between maternal attitude and compliance with the vaccination schedule was made using the nonparametric chi-square independence test with a significance level of 5% (p <0.05). The results show that: The greatest percentage (60.66%) of children under 18 months of age attending the C.S Víctor Larco not meet the immunization schedule, a low percentage of mothers (13.11%) have a favorable attitude toward immunizations, 47.54% have an attitude unfavorable and 39.34% showed an unfavorable attitude, highly significant relationship exists between the timetable of Vaccines and Immunization maternal attitude toward.